A framework to design reverse logistics operations based on circular economy values - Ripanti, Eva Faja (Cranfield University, 2016)
Reverse Logistics (RL) is complex to be managed due to the uncertainty involved e.g. the quality range of products, timing of product returns, and volume of returns. A robust RL design can contribute to increase the effectiveness of RL operations. Therefore, an RL design framework needs to be formalised. Circular economy (CE) focuses on supporting the separation of treatments between technical and biological materials in maximising the design for reuse to return to the biosphere and retain value through innovations across fields. The aim of the research is to develop a new framework to design RL operations based on CE values that can increase the effectiveness and efficiency of RL operations. This research has been conducted through the qualitative research involving cases in product recovery (PR) options that are analysed in-depth. Literature review and interview are the main methods of this research. A test was conducted by interviewing expert and respondents to obtain the expert view and test the research result which is a developed framework to design RL based on CE values. The testing engaged five criteria (usability, feasibility, consistency, effectiveness, and utility). The formal RL design framework, 15 CE values, framework to design RL based on CE values specifically PR options (repair, refurbishment, remanufacturing, and cannibalisation) are main research findings. The research contributes academically to the development of a formal RL design framework and to the identification, reformulation, redefinition, and implementation of CE values. The research can be used as a basis for an effective design of RL that takes into account the economic, environmental, and social impacts. The research can be used as a guideline or an appraisal tool in designing/modifying RL based on CE values that can support the implementation of a single RL operation and also RL based on CE.
Keywords: Circular economy; Circular economy values; Framework; Product recovery; Reverse logistics; Reverse logistics design